2010
DOI: 10.1007/s00277-010-1019-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of hydroxyurea in the treatment of the hyperproliferative manifestations of myelofibrosis: results in 40 patients

Abstract: Hydroxyurea (HU) is frequently given as treatment for myelofibrosis (MF), but data on its efficacy and tolerability are scarce. The results of HU therapy were evaluated in 40 patients with hyperproliferative manifestations of primary (n= 32), post-polycythemia vera (n= 6) or post-essential thrombocythemia (n= 2) myelofibrosis. Median interval between diagnosis and HU start was 6.2 months (range: 0-141.7). Reasons for treatment were: constitutional symptoms (55%), symptomatic splenomegaly (45%), thrombocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 29 publications
1
88
0
4
Order By: Relevance
“…An early study suggested a response rate of approximately 45% (Löfvenberg & Wahlin, 1988), although the degree of splenic reduction was not detailed. Similar findings were reported in a recent study of 18 MPN patients with symptomatic splenomegaly (Martinez-Trillos et al, 2010). Overall, complete responses are rare and doses of more than 1·5 g/d may be required to achieve clinical effect.…”
Section: Splenomegaly and Extramedullary Haemopoiesissupporting
confidence: 74%
“…An early study suggested a response rate of approximately 45% (Löfvenberg & Wahlin, 1988), although the degree of splenic reduction was not detailed. Similar findings were reported in a recent study of 18 MPN patients with symptomatic splenomegaly (Martinez-Trillos et al, 2010). Overall, complete responses are rare and doses of more than 1·5 g/d may be required to achieve clinical effect.…”
Section: Splenomegaly and Extramedullary Haemopoiesissupporting
confidence: 74%
“…2). First-line drugs of choice in such patients are hydroxyurea for symptomatic splenomegaly [125], androgens preparations [126], prednisone [126], danazol [127], thalidomide 6 prednisone [128][129][130] or lenalidomide 6 prednisone [131,132] for symptomatic anemia, splenectomy (or splenic radiotherapy for nonsurgical candidates) for splenomegaly that is resistant to conventional drug therapy [133], involved field radiotherapy for nonhepatosplenic EMH might and ruxolitinib for severe constitutional symptoms that are resistant to hydroxyurea therapy [133].…”
Section: Myelofibrosismentioning
confidence: 99%
“…37 Indeed, results from the randomized COMFORT-II study indicated that none of the patients in the best-available therapy arm presented measurable improvements in symptoms, as measured by the EORTC QLQ-C30 or FACT-Lym scores. 34 Low-dose prednisone may sometimes produce a feeling of well-being, but the effect is usually modest and transient.…”
Section: Constitutional Symptomsmentioning
confidence: 99%